PREVENTION OF CARDIO-VASCULAR DISEASES - S.G Yo’ldosheva; D.A. Kasimova (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The human cardiovascular system, which was formed in the process of biological evolution, has not changed significantly throughout the history of mankind. But our way of life is very different from the way of life of our distant, and even not very distant, ancestors. Then movement, obtaining food, creating housing and all other types of activity required constant and large expenditures of muscle strength from a person. And the human circulatory system is initially oriented precisely towards such an intensely active lifestyle. For its normal functioning, for example, a person must walk at least 6 km a day, and this is daily! By our urban standards today, many people cannot afford to walk even one or two bus stops; there is no time for it